Analysis of solution stability in Al2 O3-Cu/H2O over a stretching/shrinking wedge - Nurul Amira, Zainal; Khashi’ie, Najiyah Safwa; Waini, Iskandar; Khairum, Hamzah; Sayed Kushairi, Sayed Nordin; Abdul Rahman, Mohd Kasim; Roslinda, Mohd Nazar; Pop, Ioan Mihai (Semarak Ilmu Publishing, 2023)
In this study, the stability analysis is conducted in order to observe the reliability of the generated solutions. The influence of several parameters is taken into consideration including heat source/sink parameter, suction, magnetic field, and heat transfer. The well-known heat transfer fluid that is Al2O3-Cu/H2O hybrid nanofluid past a stretching/shrinking wedge is implied. The similarity equations are achieved after implying suitable similarity transformation which then needed to be solved numerically using bvp4c, embedded in MATLAB software. Dual solutions are observed along the investigation within specified values of involved parameters. It is important to note that verification results show excellent concordance with pre-existing reports.